Tinjauan Kesiapan Belajar dalam Proses Transisi Pendidikan Anak Usia Dini ke Sekolah Dasar - Siti Fatimah Soenaryo; Susanti, Reni Dwi; Beti Istanti Suwandayani (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The provision of proper education for children is an essential responsibility in order to cultivate high-quality human resources. Early Childhood Education (PAUD) offers children a conducive learning environment, motivation to learn, and guidance to optimize their development. Strengthening the transition from PAUD to primary school is an activity aimed at enhancing PAUD and ensuring teachers have a solid foundation in delivering education at the elementary school level. This qualitative research aims to examine the readiness of children in facing the transition from PAUD to elementary school. The research adopts a descriptive approach and involves teachers at both PAUD and elementary school level 1 as subjects. The data collection techniques employed include interviews and questionnaires. The findings of the study reveal that in preparing for the transition, three key preparations are necessary: the readiness of the children themselves, supportive parents, and a well-prepared school environment. Emotional maturity of the child, parental support, and school readiness encompassing infrastructure, learning environment, and teacher competence in classroom management are crucial factors in this regard.